(untitled) (Journal of the College of Basic Education, 2024)
Attention is one of the most important mental processes that play an important role in the cognitive development of the student, as he can select sensory stimuli that help him acquire skills and form the right behavioral habits in order to adapt to the surrounding environment, and although attention is a developmental mental process, but we may find the inability of students to focus their attention or organize their mental activity towards a certain thing for a period, with their inability to identify external distracting factors, and they move excessive movements without a goal. the problem of research lies in that the problems facing specialists in the process of teaching is how to measure mental abilities and the ability to There is also the lack of accurate objective tests that rely on electronic devices to measure them, as well as" if there are such tests, they do not have criteria that enable the teacher to assess the student’s current condition. The research aims to design and standardize a computerized test to measure the distraction of attention for sixth grade primary school students and to find the standards of grades and levels for the computerized test.the researchers concluded that a computerized system was designed to measure the concentration of attention for sixth grade primary school students and to find the standards represented by grades and levels for this computerized test.